2011
DOI: 10.1501/egifak_0000001226
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of university students’ internet and game addiction with respect to several variables

Abstract: ABSTRACT. The purpose of this study was to investigate whether internet and game addiction of university students differ in regard to variables such as gender, grade, having computer and internet connection and game type which they prefer. The sample of this study consists of 996 students from Faculty of Educational Science at Ankara University and Education Faculty at Gazi University. In terms of gender variable, male students' internet and computer game addiction levels were significantly higher than females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
(35 reference statements)
5
8
0
4
Order By: Relevance
“…Male participants were found to have higher digital game addiction points averages than female participants. In a study similar to our study (Inal and Cağıltay, 2005;Cakır et al, 2011;Horzum, 2011;Sahin and Tugrul, 2012;Li and Wang, 2013) the average game addiction scores were higher in boys than girls.…”
Section: Discussionsupporting
confidence: 83%
“…Male participants were found to have higher digital game addiction points averages than female participants. In a study similar to our study (Inal and Cağıltay, 2005;Cakır et al, 2011;Horzum, 2011;Sahin and Tugrul, 2012;Li and Wang, 2013) the average game addiction scores were higher in boys than girls.…”
Section: Discussionsupporting
confidence: 83%
“…When it is tested whether internet addiction differs according to gender, it is concluded that male participants have higher internet addiction based on social problems than female participants. This result is supported by the literature (Shotton, 1991;Scherer & Bost, 1997;Chou & Hsiao, 2000;Morahan-Martin & Schumacher 2000, Vaizoğlu et al, 2004Kaltiala-Heino, Lintonen & Rimpela, 2004;Chou, Condron & Belland 2005;Ha, et al, 2007;Korkeila et al, 2010;Çakır, Ayas & Horzum, 2011;Li et al, 2013;Pawlikowski, Altstötter-Gleich & Brand, 2013). According to the results obtained in the research, male participants prefer to spend more time on the internet instead of going out with others.…”
Section: Tartışma Ve Sonuçsupporting
confidence: 84%
“…İnternet bağımlılığının cinsiyete göre farklılaşıp farklılaşmadığı test edildiğinde erkek katılımcıların sosyal problemlere dayalı internet bağımlılıklarının kadın katılımcılara göre daha yüksek olduğu sonucuna ulaşılmıştır. Bu sonuç literatür tarafından da desteklenmektedir (Shotton, 1991;Scherer & Bost, 1997;Chou & Hsiao, 2000;Morahan-Martin & Schumacher 2000, Vaizoğlu vd., 2004Kaltiala-Heino, Lintonen & Rimpela, 2004;Chou, Condron & Belland 2005;Ha, vd., 2007;Korkeila vd., 2010;Çakır, Ayas & Horzum, 2011;Li vd., 2013;Pawlikowski, Altstötter-Gleich & Brand, 2013). Cinsiyetler arasında fark bulunmadığını gösteren çalışmalar da mevcuttur (Brenner, 1997;Hall & Parsons, 2001;Subrahmanyam & Lin, 2007;Batıgün & Hasta, 2010).…”
Section: Tartışma Ve Sonuçunclassified
“…Cinsiyet değişkeni gibi bireysel farklılıkların, bireyin teknoloji kabullerini ve teknoloji kullanımına yönelik niyetlerini açıklamak amacıyla ortaya çıkan ve birçok kuramsal modelin birleşimi olan Teknoloji Kabul ve Kullanım Birleştirilmiş Modeli-2 (UATAUT-2)'de (Venkatesh, Thong ve Xu, 2012) de cinsiyet değişkeninin ilişkileri düzenlemede önemli bir etken olduğu varsayımı ifade edildiğinden (Chang, 2012;Palau Saumell, Forgas Coll, Sanchez Garcia ve Robres, 2019;Yılmaz ve Kavanoz, 2017), bu sebeple öğrencilerin siberaylaklık davranışında bulunma durumları üzerinde cinsiyet etkisi araştırılmıştır. Cinsiyet etkisine yönelik elde edilen bulgunun ortaya çıkma sebebi, erkeklerin teknolojiye daha meraklı olmaları, akıllı telefonlarında birçok yeni uygulamayı kullanmaları ve internet bağımlılığı ve oyun bağımlılığı konusunda kızlara nazaran daha yatkın olmaları nedeniyle (Aljomaa vd., 2016;Çakır, Ayas ve Horzum, 2011;Griffiths, Kuss ve King, 2012;Oggins ve Sammis, 2012) siberaylaklık davranışında bulunma olasılıklarının da kızlara oranla daha yüksek olabileceği fikri ile açıklanabilir. Benzer şekilde alanyazında da birçok çalışmada, cinsiyetin siberaylaklık davranışı üzerinde önemli bir etkisinin olabildiği bulgusuna ulaşılmıştır (Ahmad ve Omar, 2017;Akbulut vd., 2017;Andreassen vd., 2014;Arabacı, 2017;Baturay ve Toker, 2015;Blanchard ve ve Henle, 2008;Garrett ve Danziger, 2008;Hayıt ve Dönmez, 2016;Keser vd., 2016;Lim ve Chen, 2012;Dursun vd., 2018;Vitak vd., 2011).…”
Section: Tartışma Sonuç Ve öNerilerunclassified